Determinants for the humanitarian workforce in migrant health at the US-Mexico border: optimizing learning from health professionals in Matamoros and Reynosa, Mexico - Reynolds, Christopher W.; Ryan, Savannah F.; Acharya, Eesha; Berberoglu, Ipek; Bishop, Samuel; Tucker, Brendon; Barreto-Arboleda, Juan Daniel; Ibarra, Jorge Armando Flores; Vera, Penelope; Orozco, Laura Jocelyne Fuentes; Draugelis, Sarah; Mohareb, Amir M.; et al. (Frontiers in Public Health, 2024)
Introduction Shortages of health professionals is a common problem in humanitarian settings, including among migrants and refugees at the US-Mexico border. We aimed to investigate determinants and recruitment recommendations for working with migrants to better understand how to improve health professional participation in humanitarian efforts. Methods Semi-structured interviews were conducted with health professionals working with migrants at the US-Mexico border in Matamoros and Reynosa, Mexico. The study aimed to identify motivations, facilitators, barriers, and sacrifices to humanitarian work, and recommendations for effective learning approaches to increase participation. Participants included health professionals working within humanitarian organizations to deliver healthcare to migrants living in non-permanent encampments. Interviews lasted approximately 45 min and were analyzed in NVivo14 using a validated codebook and team-based methodology. Results Among 27 participants, most were female (70%) with median age 32. Health professionals included nurses (41%), physicians (30%), logisticians (11%), social workers (7%), an EMT (4%), and a pharmacist (4%) from the US (59%), Mexico (22%), Cuba (11%), Peru (4%), and Nicaragua (4%) working for four organizations. Participants expressed internal motivations for working with migrants, including a desire to help vulnerable populations (78%), past experiences in humanitarianism (59%), and the need to address human suffering (56%). External facilitators included geographic proximity (33%), employer flexibility (30%), and logistical support (26%). Benefits included improved clinical skills (63%), sociocultural learning (63%), and impact for others (58%). Negative determinants included sacrifices such as career obligations (44%), family commitments (41%), and safety risks (41%), and barriers of limited education (44%) and volunteer opportunities (37%). Participants criticized aspects of humanitarian assistance for lower quality care, feeling useless, and minimizing local capacity. Recommendations to increase the health workforce caring for migrants included integration of humanitarian training for health students (67%), collaborations between health institutions and humanitarian organizations (52%), and improved logistical and mental health support (41%). Conclusion Health professionals from diverse roles and countries identified common determinants to humanitarian work with migrants. Recommendations for recruitment reflected feasible and collaborative approaches for professionals, organizations, and trainees to pursue humanitarian health. These findings can be helpful in designing interventions to address workforce shortages in humanitarian migrant contexts.